Posttransplant Lymphoproliferative Disorder Involving the Gastrointestinal Tract - Kirtane, Tejas; Uberoi, Guneesh S.; Uberoi, Angad S.; Loghavi, Sanam; Medeiros, L. Jeffrey; Bhutani, Manoop S. (Journal of Digestive Endoscopy, 2020)
Posttransplant lymphoproliferative disorder (PTLD) is a rare and life-threatening complication of both solid organ transplantation and hematopoietic stem cell transplantation. In most cases, PTLD develops in Epstein–Barr virus (EBV)-seropositive individuals in the setting of chronic immunosuppression and decreased T-cell surveillance. Clinical manifestations of PTLD may be nonspecific, resembling primary EBV infection (fever, night sweats, malaise, and cervical lymphadenopathy), or it can involve the central nervous system, bone marrow, kidneys, liver, lungs, and gastrointestinal tract. Gastrointestinal symptoms in the posttransplant setting may indicate underlying PTLD, and it is important for physicians to be able to recognize its appearance on endoscopy.
Keywords: Epstein–Bar virus; hematopoietic stem-cell transplantation; posttransplant lymphoproliferative disorder; solid-organ transplantation